2021
DOI: 10.1371/journal.pone.0248576
|View full text |Cite
|
Sign up to set email alerts
|

Factors that influence market participation among traditional beef cattle farmers in the Meatu District of Simiyu Region, Tanzania

Abstract: Market participation among beef cattle farmers is key to ensuring better income, food security, and sustainable beef supply. Farmers in the traditional beef cattle sector, nevertheless, are well known for their low market participation. This study, thus, sought to examine factors that influenced market participation among beef cattle farmers in the Meatu district of Simiyu region, Tanzania. The study randomly selected a sample size of 393 farmers. The cross-sectional data collected through interviews and quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 8 publications
1
27
0
Order By: Relevance
“…About 59.3% of pastoralists had no formal education, while 35.5% and 5.5% of pastoralists, had primary and college education, respectively. Education improves one's ability to improve beef cattle productivity and profitability [31]. Pastoralists should be provided with tailor-made training and education to promote the development of the beef cattle production among pastoralists.…”
Section: ( ) = (8)mentioning
confidence: 99%
See 1 more Smart Citation
“…About 59.3% of pastoralists had no formal education, while 35.5% and 5.5% of pastoralists, had primary and college education, respectively. Education improves one's ability to improve beef cattle productivity and profitability [31]. Pastoralists should be provided with tailor-made training and education to promote the development of the beef cattle production among pastoralists.…”
Section: ( ) = (8)mentioning
confidence: 99%
“…The average grazing land owned by pastoralists was 10.9 ha. Grazing land availability is important in beef cattle productivity and profitability, which enhances the economic benefits and efficiency of beef cattle production [31].…”
Section: ( ) = (8)mentioning
confidence: 99%
“…It was relevant with previous study [23] The previous research reported that there is a tendency of market domination from wholesalers, so it can control price of beef cattle in its marketing chain. While, the participation of traditional farmers is heavily influenced by access to market information, low education background, and agriculture credit [7,24,25]. The marketing margin in the level of livestock brokers or intermediaries was relatively small since they only bore a lower marketing cost, such as market retribution cost and temporary gathering cost of beef cattle.…”
Section: Marketing Marginmentioning
confidence: 99%
“…The characteristic of breeder's and trader's income of beef cattle in North Sulawesi shows that the rate of income was IDR 2,500,000-IDR 10,000,000/month. Therefore, breeders and traders sufficiently relied on beef cattle as one of the main household livings, even though it had not become the only living source of breeder's household [6,7,9]. It happened since some of the breeders still counted on foods plant as the main source of living.…”
Section: Characteristics Of Respondentmentioning
confidence: 99%
“…In North Sulawesi, the sub-sector of beef cattle contributes to household income, regional income, job procurement ad export profit [2,3,4]. As beef cattle has a significant role in the level of household, it effects on the socio-economic life, such as solving household's economic issues, assets enhancer of household's wealth and value depositor when the market and formal financial institution are unavailable [5,6,7].…”
Section: Introductionmentioning
confidence: 99%